Impacts of Sea Land Breeze on the Fog and PM2.5 Concentration in Tianjin, China - Lihong Meng; Erhui Yang; Lili Liu; Wei Wang; Jianbo Yang; Ping Qu (Aerosol and Air Quality Research)
Abstract Sea land breeze (SLB) are mesoscale circulation phenomena that significantly affect weather and air quality in coastal regions. A detailed analysis of SLB circulation was conducted. We focused on the impacts of SLB on the formation of fog and the PM2.5 concentration through vertical observation. The SLB transported the water vapor between the land and sea. The land breeze transported the water vapor over the city to the sea at first, which provided favorable water vapor conditions for the formation of the Bohai sea fog. Then the continuous sea breeze carried the water vapor from the sea to the land, promoting the landing of sea fog and forming the coastal urban fog in Tianjin. The vertical height of the sea breeze reached about 1200 m. The transportation of continuous water vapor and 90 m thick temperature inversion were the two main causes for the formation of coastal urban fog. PM2.5 concentration in coastal city increased to the high value due to regional pollutant transportation and increasing of humidity before the formation of fog. When fog and haze coexisted and the fog top was below the inversion layer, the fog played the role of accumulation on PM2.5 concentration. As the sea breeze intensified, it transported PM2.5 from lower layers to higher altitudes, resulting in lower PM2.5 concentration near the ground and higher concentration above within the boundary layer. This indicated that the mesoscale circulation of SLB played an important role when the large-scale meteorological conditions were relatively weak.